Evaluation of antioxidant and anticancer activities of families Lamiaceae and Caryophyllaceae - Bohdanovych, T.; Baranovsky М.; Karandey, D. (Problems of Environmental Biotechnology, 2019)
Article presents the results of experimental investigation of antioxidant and anticarcinogenic activity of plant extracts of families Lamiaceae and Caryophyllaceae. Selected species are: Salvia officinalis, Origanum vulgare, Melissa officinalis, Stellaria media. The determination of ascorbic acid content and total phenols content is carried out. Cytotoxic activity of plant extracts is evaluated using WISH cell lines. The following methodologies are concidered: spectrophotometry; photoelectric colorimetry; microscopic method based on inhibition and quantification of cancer cell lines.